ANALISA PENGARUH FAKTOR HARGA, KUALITAS PRODUK DAN KELENGKAPAN PRODUK TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN - Susanto, Frengki adi; Maruto, IGN Anom; Novaria, Rachmawati (Universitas 17 Agustus 1945 Surabaya, 2018)
This research entiled “ The Influence Factor of Price, Product Quality and Product Completeness on Purchase Decision ( Case Study At Hokky Supermarket in Surabaya ) “. The population in this study were consumers who had been shopping at Hokky Swalayan in Surabaya aged 17 year. Sampel taken as many as one hundred respondents. The variables used are price, product quality, product completeness and purchasing decision.This result can be concludes as follows: There is influence of individual price toward purchasing dicision proven and accepted reality of partial test result (t) obtained with significant level <0,05, there is individual influence of product quality to purchasing decision proven and accepted reality partial test result (t) is obtained with significant level <0,05, there is individual influence of product completeness to proven purchasing decision and accept reality of partial test result (t) obtained with significant level <0,05.This shows that there are problem with purchasing decisions. The main problem to note is the price factor that still many weakness because is that the lowers level of influence than the factor of product quality and completeness of the product.Keywords : Price, Product Quality, Product Completeness and Consumer Purchasing Decision